Crystal Structures and Phase‐Transition Dynamics of Cobaltocenium Salts with Bis(perfluoroalkylsulfonyl)amide Anions: Remarkable Odd–Even Effect of the Fluorocarbon Chains in the Anion. Issue 20 (9th April 2013) - Mochida, Tomoyuki; Funasako, Yusuke; Inagaki, Takashi; Li, Meng‐Jiao; Asahara, Kotaro; Kuwahara, Daisuke
Abstract Crystal structures and thermal properties of cobaltocenium salts with bis(perfluoroalkylsulfonyl)amide (CnF2n+1SO2)2N anions [n=0 (1), 1 (1 a), 2 (1 b), 3 (1 c), and 4 (1 d)] and the 1, 1, 2, 2, 3, 3‐hexafluoropropane‐1, 3‐disulfonylamide anion (2) were investigated. In these solids, the cations are surrounded by four anions around their C5 axis, and stacking of these local structures forms two kinds of assembled structures. In the salts with even n (1, 1 b, and 1 d), the cation and anion are arranged alternately to form mixed‐stack columns in the crystal. In contrast, in the salts with odd n (1 a and 1 c), the cations and anions independently form segregated‐stack columns. An odd–even effect was also observed in the sum of the phase‐change entropies from crystal to melt. All of the salts exhibited phase transitions in the solid state. The phase transitions to the lowest‐temperature phase in 1, 1 a, and 2 are accompanied by order–disorder of the anions and symmetry lowering of the space group, which results in the formation of an ion pair. Solid‐state 13C NMR measurements on 1 a and 1 b revealed enhanced molecular motions of the cation in the higher‐temperature phases.